2018
DOI: 10.1002/jcp.26848
|View full text |Cite
|
Sign up to set email alerts
|

The protective role of curcumin in myocardial ischemia–reperfusion injury

Abstract: Coronary artery disease (CAD) is a well-known pathological condition that is characterized by high morbidity and mortality. The main pathological manifestation of CAD is myocardial injury due to ischemia-reperfusion (I-R). Currently, no efficacious treatment of protecting the heart against myocardial I-R exists. Hence, it is necessary to discover or develop novel strategies to prevent myocardial-reperfusion injury to improve clinical outcomes in patients with CAD. A large body of experimental evidence supports… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
92
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 176 publications
(93 citation statements)
references
References 68 publications
(128 reference statements)
1
92
0
Order By: Relevance
“…Unsolved and complex MI/R injury, which has been identified as a major factor contributing to mortality, morbidity and disability worldwide, is also a major cause of death in cardiovascular disease patients, leading to severe damage to the myocardium when serious myocardial infarction occurs [7][8][9]. Moreover, there is no practical solution for thoroughly avoiding MI/R injury [10]. In this context, novel therapeutic strategies for MI/R injury are urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Unsolved and complex MI/R injury, which has been identified as a major factor contributing to mortality, morbidity and disability worldwide, is also a major cause of death in cardiovascular disease patients, leading to severe damage to the myocardium when serious myocardial infarction occurs [7][8][9]. Moreover, there is no practical solution for thoroughly avoiding MI/R injury [10]. In this context, novel therapeutic strategies for MI/R injury are urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Preventing the occurrence of cardiomyocyte apoptosis has become a target for certain drugs that interfere with MIRI (14,15). It has been reported that curcumin is a potent cardioprotective compound, which may have beneficial effects on MIRI by reducing oxidative stress, preventing inflammation and inhibiting cardiomyocyte apoptosis (16). Numerous studies have indicated that traditional Chinese medicine (TCM) exerts a potent cardioprotective effect on MIRI and may be used as a therapeutic approach for its treatment (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…The main pathological manifestation of coronary artery diseases is myocardial injury due to I‐R. Recently, an increasing number of studies, both in vitro and in vivo, revealed that curcumin exerts a potent cardioprotective effect on myocardial I‐R injury, mainly through prevention of inflammation and reduction of oxidative stress (Mokhtari‐Zaer, Marefati, Atkin, Butler, & Sahebkar, ). It is reported that curcumin can improve myocardial I‐R injury by increasing antioxidative activity as evidenced by elevated mitochondrial superoxide dismutase (SOD) and decreased mitochondrial hydrogen peroxide and malondialdehyde (MDA) levels (Y. Yang et al, ).…”
Section: Antioxidative and Anti‐inflammatory Properties Of Curcumin Imentioning
confidence: 99%